When to set a net-zero greenhouse gas emissions target year : information and analysis to support discussion of the Climate Change (Emissions Reduction Targets) (Scotland) Bill.: information and analysis to support discussion of the Climate Change (Emissions Reduction Targets) (Scotland) Bill. (2018) - Unknown
No abstract available